2016
DOI: 10.1002/marc.201600281
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Silicone Poly‐HIPEs with Controlled Pore Sizes via Reactive Emulsion Stabilization

Abstract: Macrocellular silicone polymers are obtained after solidification of the continuous phase of a poly(dimethylsiloxane) emulsion, which contains poly(ethylene glycol) drops of sub-millimetric dimensions. Coalescence of the liquid template emulsion is prohibited by a reactive blending approach. The relationship is investigated in detail between the interfacial properties and the emulsion stability, and micro- and millifluidic techniques are used to generate macrocellular polymers with controlled structural proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
(46 reference statements)
2
24
0
2
Order By: Relevance
“…Comparing the properties for different pairs of immiscible polymers stabilized by either premade copolymers or in-situ formed copolymers shows that the equilibrium interfacial values are identical with both stabilization routes. For example, Wagner et al [87] measured the interfacial tension between PDMS and PEG with pre-made PDMS-PEG-PDMS and found equilibrium values close to the ones which Giustiniani et al [81] found for PDMS and PEG stabilized by in-situ compatibilization ( Figure 5). As the configuration of the copolymers, in addition to their chemical composition, has an impact on the equilibrium value of interfacial tension γ eq [86,88,89], the comparisons between the reactive and non-reactive cases is not straightforward.…”
Section: Equilibrium Interfacial Tensionmentioning
confidence: 55%
See 1 more Smart Citation
“…Comparing the properties for different pairs of immiscible polymers stabilized by either premade copolymers or in-situ formed copolymers shows that the equilibrium interfacial values are identical with both stabilization routes. For example, Wagner et al [87] measured the interfacial tension between PDMS and PEG with pre-made PDMS-PEG-PDMS and found equilibrium values close to the ones which Giustiniani et al [81] found for PDMS and PEG stabilized by in-situ compatibilization ( Figure 5). As the configuration of the copolymers, in addition to their chemical composition, has an impact on the equilibrium value of interfacial tension γ eq [86,88,89], the comparisons between the reactive and non-reactive cases is not straightforward.…”
Section: Equilibrium Interfacial Tensionmentioning
confidence: 55%
“…Experiments show that the relaxation of the interfacial tension of reactive interfaces exhibits a strikingly similar behaviour to that of non-reactive interfaces [81][82][83][84][85][86]. All curves start at a value γ 0 , which is the value of interfacial tension between the two non-reactive phases with no added surfactants.…”
Section: Equilibrium Interfacial Tensionmentioning
confidence: 99%
“…Theb iggest disadvantage of this technique is the necessity to remove the dispersed phase, which makes this acost-inefficient procedure for the production of large samples.However,applications are beginning to emerge in which the presence of the dispersed liquid is actually desired. Forexample,the viscosity of the drops allows the adhesive properties of solid silicone emulsions to be tuned, [42] and electrolyte-filled porous polymers can be directly processed into electrode separators in batteries. [43,44]…”
Section: Methodsmentioning
confidence: 99%
“…B. eine Feineinstellung der adhäsiven Eigenschaften von festen Siliconemulsionen, [42] und Elektrolyt-gefüllte porçse Polymere kçnnen direkt als Elektrodenseparatoren in Batterien verwendet werden. Die Funktion der beiden Flüssigkeiten (interne oder kontinuierliche Phase) kann durch einen entsprechend ausgewählten Emulgator recht einfach umgekehrt werden.…”
Section: Flüssigtemplatroutenunclassified
“…Die Viskositätd er Tropfen ermçglicht z. B. eine Feineinstellung der adhäsiven Eigenschaften von festen Siliconemulsionen, [42] und Elektrolyt-gefüllte porçse Polymere kçnnen direkt als Elektrodenseparatoren in Batterien verwendet werden. [43,44] Abbildung 4.…”
Section: Flüssigtemplatroutenunclassified